A novel pre-magnetized ZVI/PS pretreatment for improving sludge dewaterability: The role of EPS fractions. (15th September 2022) - Ling, Xiao; Chen, Minjie; Cai, Anhong; Sun, Honglei; Xu, Shanlin; Wang, Lei; Li, Xueyan; Deng, Jing
Abstract: The dewaterability of waste-activated sludge (WAS) has been extensively examined using zero-valent iron (ZVI)-based advanced oxidation processes (AOPs). However, the high dosage and low utilization efficiencies of ZVI cast doubt on the dependability and viability of ZVI-based AOPs. In this study, we successfully demonstrated pre-magnetization as an efficient, chemical-free, and ecological method for improving the efficiency of sludge dewatering by ZVI/persulfate (PS) process, in which the reduction ratios of capillary suction time (CST) and specific resistance to filtration (SRF) increased by 8.67% and 11.06% under optimal conditions, respectively. The highly active Fe 2+ released during ZVI corrosion may be more essential than ZVI itself during PS activation, which could be strengthened by pre-magnetization. Both homogeneous and heterogeneous Fe 2+ could react with PS to produce aqueous hydroxyl radicals (∙OH) and sulfate radicals (SO4 − ∙) as well as surface-bound ∙OH and SO4 − ∙, further decomposing bound-extracellular polymeric substances fractions, broking hydrophilic functional groups and compounds, altering protein secondary structure to expose more hydrophobic sites, and releasing abundant EPS-bound water. Due to the protection of tightly-bound extracellular polymeric substances (TB-EPS) and the competitive oxidation of organics released during the early disintegration stage, radical oxidation primarily occurs at extracellular levels, releasing a bit of intracellular water. Besides, polysaccharides in TB-EPS may function a more significant role in flocculation than proteins, and a porous structure favorable to drainage will be formed after the pre-magnetized ZVI/PS treatment. The cost-benefit analysis further reveals that the Pre-ZVI/PS process presents high reusability and utilization, making it potential for particle application in sludge dewatering. Graphical abstract: Image 1 Highlights: Pre-magnetized ZVI/PS pretreatment significantly improved sludge dewaterability. Pre-magnetization enhanced ZVI reactivity efficiently due to local corrosion. EPS migration and dissolved EPS mineralization occurred during sludge breakdown. Radical oxidation and Fe 2+/3+ re-flocculation enhanced sludge dewatering. EPS fractions affected the distribution of various types of bound water in sludge.